2022
DOI: 10.1177/0306624x221132218
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Health Status of Women in Prison: A Comparison between Drug Users versus Non-users

Abstract: This study aims to analyze the history of substances use, clinical diagnoses, contacts with healthcare, and health complaints. Also, it aims to compare the health status of substance users versus non-users. Health records of 93 detained women from a prison in northern Portugal, with a mean age of 38.02 years old, were reviewed and coded using both International Classification of Primary Care—2 and International Classification of Diseases—10th. Data revealed high percentages of detainees with a history of subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…It also diminishes their ability to build and maintain positive relationships with fellow inmates and prison staff, creating a socially challenging environment for them to receive support and solidarity (Moore et al, 2021;Zielinski et al, 2021). Furthermore, some studies have found that the sustained effects of violence within women's prisons can heighten the complexity of reintegration due to the development of low self-esteem, social isolation, and strong negative stigma against former inmates in society (Alves et al, 2022;Augsburger et al, 2022;Camplain et al, 2022;Shoham & Timor, 2014). Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…It also diminishes their ability to build and maintain positive relationships with fellow inmates and prison staff, creating a socially challenging environment for them to receive support and solidarity (Moore et al, 2021;Zielinski et al, 2021). Furthermore, some studies have found that the sustained effects of violence within women's prisons can heighten the complexity of reintegration due to the development of low self-esteem, social isolation, and strong negative stigma against former inmates in society (Alves et al, 2022;Augsburger et al, 2022;Camplain et al, 2022;Shoham & Timor, 2014). Figure 2.…”
Section: Introductionmentioning
confidence: 99%